Lattice innovative flow diverter with mechanical balloons: a new breakthrough and efficacy evaluation in the treatment of unruptured intracranial aneurysms - Sun, Xufeng; Peng, Yueyang; Li, Bin; Zhang, Mengyuan; Wen, Zhifeng (Frontiers in Medicine, 2025)
PurposeThe Lattice Innovative Flow Diverter with Mechanical Balloons (Lattice FD-MB) provides superior positioning accuracy and wall apposition during deployment, potentially addressing the limitations of traditional mesh stents in treating complex lesions. However, clinical data on the efficacy and safety of the Lattice FD-MB for unruptured intracranial aneurysms (UIAs) remain limited. This study evaluates the effectiveness and safety of the Lattice FD-MB in UIA treatment.MethodsWe retrospectively analyzed 29 UIA patients treated with the Lattice FD-MB at our institution between October 2023 and October 2024. After the operation, digital subtraction angiography (DSA) and computed tomography angiography (CTA) were performed to assess aneurysm occlusion. Clinical follow-up, including modified Rankin scale (mRS) scores and DSA, was conducted at 3, 6, and 12 months postoperatively.ResultsThe Lattice FD-MB was successfully deployed in all patients, achieving a 100% procedural success rate with no intraoperative device-related failures. Intraoperative complications occurred in two cases (6.9%). Postoperatively, 27 patients (93.1%) showed favorable clinical outcomes, defined as no new neurological deficits or hemorrhagic/ischemic events. At discharge, functional outcomes (mRS) were as follows: mRS 0 (no symptoms) in 23 patients (79.3%), mRS 1 (no significant disability) in 3 patients (10.3%), and mRS 2 (slight disability) in 3 patients (10.3%). On follow-up, the proportion of patients with mRS 0 increased over time, with 82.8% (24/29) at 3 months, 86.2% (25/29) at 6 months, and 89.7% (26/29) at 12 months, demonstrating sustained clinical stability and neurological improvement.ConclusionThe Lattice FD-MB appears to be a feasible and safe treatment for UIAs, with promising patient outcomes. Further research is warranted to investigate prognostic factors influencing long-term results after Lattice FD-MB treatment.